Single and joint effects of perchlorates to daphnia magna: additivity and interaction patterns - Loureiro, Susana (2020)
Frequent cases of soil and water contamination by perchlorates, and consequent toxicity to plants, animals and humans have drawn attention worldwide. Anthropogenic actions are the main cause for this pollution. Due to high levels of oxidation, perchlorates are commonly used to produce solid propellants for rockets and missiles, fireworks, and air bag inflators and also as bleach in paper industry. In this work we assessed the effects of ammonium and sodium perchlorates singly and in mixture to Daphnia magna by studying the endpoints: immobilization, reproduction, growth and feeding activities. At short time exposures characterized with immobilization and feeding parameters, ammonium perchlorate was 10 times more toxic to D. magna than sodium perchlorate. On the other hand, toxicity was similar when a long-term exposure with reproduction parameter was carried out. The mixture toxicity approach also showed that sodium perchlorate was ruled for synergistic patterns when dominant in the short-term exposure tests. When evaluating the reproductive effort by using the number of neonates, the concentration addition model was the best fit. This study shows that the different properties of two chemicals, highlighting the possible synergy that can occur when chemicals are present in mixtures, will be of high relevance to improve Cumulative Risks assessment procedures.